The Effect of Glass and Kevlar Fiber Volume Fraction on the Mechanical Properties of Epoxy Composites - Louka, Elias; Papadakis, Loucas; Georgiades, George P.; Yiatros, Stylianos; Osman, Hamza; Xuan, Jianping (My University, 2024)
The effect of glass and Kevlar fiber volume fraction on the mechanical properties of epoxy composites, was investigated in this study. Different number of layers, total mass of the non-impregnated fibers and reinforcing materials were used to create the specimens. As a result of the different number of the layers, specimens with varying thickness and total composite mass were produced. Volume fraction was changed, depends on these parameters. Specimens of fiber glass and Kevlar were prepared using the vacuum banging method and epoxy resin as the matrix material. The mechanical behaviors of the specimens were tested under uniaxial tension and three-point bending. Specifically, the samples’ stiffness and strength, were examined.The aspects of varying layers, fiber properties, thickness of sample and mass of fibers and total composite, i.e. volume fraction was found to play an important role for the design of a composite with an optimized stiffness or strength-to-weight ratio.